CD3+ Macrophages Deliver Proinflammatory Cytokines by a CD3- and Transmembrane TNF-Dependent Pathway and Are Increased at the BCG-Infection Site - Rodriguez-Cruz, Adriana; Vesin, Dominique; Ramon-Luing, Lucero; Zuñiga, Joaquin; Quesniaux, Valérie F. J.; Ryffel, Bernhard; Lascurain, Ricardo; Garcia, Irene; Chávez-Galán, Leslie (Frontiers in Immunology, 2019)
Macrophages are essential cells of the innate immune response against microbial infections, and they have the ability to adapt under both pro- and anti-inflammatory conditions and develop different functions. A growing body of evidence regarding a novel macrophage subpopulation that expresses CD3 has recently emerged. Here, we explain that human circulating monocytes can be differentiated into CD3+TCRαβ+ and CD3+TCRαβ- macrophages. Both cell subpopulations express on their cell surface HLA family molecules, but only the CD3+TCRαβ+ macrophage subpopulation co-express CD1 family molecules and transmembrane TNF (tmTNF). CD3+TCRαβ+ macrophages secrete IL-1β, IL-6 IP-10 and MCP-1 by both tmTNF- and CD3-dependent pathways, while CD3+TCRαβ- macrophages specifically produce IFN-γ, TNF and MIP-1β by a CD3-dependent pathway. In this study, we also used a mouse model of BCG-induced pleurisy and demonstrated that CD3+ myeloid cells (TCRαβ+ and TCRαβ- cells) are increased to the infection sites during the acute phase (2 weeks post-infection). Interestingly, cell increment was mediated by tmTNF, and the soluble form of TNF was dispensable. BCG-infection also induced the expression of TNF receptor 2 on CD3+ myeloid cells, which increased after BCG-infection, suggesting that the tmTNF/TNFRs axis plays an important role in the presence or function of these cells in tuberculosis.